Performance measurement and evaluation for charities. - Lin, Jingyi. (2008)
With the eruption of NKF controversy in 2005, more donors are concerned about disclosures and performance measurements of charities. The authors believed the necessity to come up with a set of performance measurements for charities, with the use of publicly available information.